Tax and Poverty in Indonesia - Lydia Ivana Kumajas; Steven Tumbelaka; Merry L. Kumajas (AIBPM Publisher, 2018)
Tax is one of the financial resources, taxes were expected to have a positive impact on reducing poverty. It is assumed poverty will be reduced through improved health and education. The Indonesian government tried to increase its revenues through taxes. Various regulations were made even at the same time various cases were found which reduced public trust in tax utilization. Government efforts were proved successful in increasing the state revenues from the tax sector. Visible from the increase in realization of tax revenues from 2007 to 2016, the tax income was expected to be followed by an increased public trust of tax utilization. In turn, increasing tax income is expected to improve welfare. The welfare of Indonesian population, can be seen from several indicators of social issue and population density in poverty, education and health. Government assistance through various health and education funds both cash money and non-cash could have an impact on the declining number of poor people in Indonesia. The aim of this study, were to obtain observed data of positive effect tax income on reducing of the number of poverties, through improving education and health. This research was expected provide an overview of the benefits of public compliance in paying taxes, and as the result of evaluating the use of tax in an effort to reduce the number of poor people in Indonesia. The observation data used 2018 Indonesia Statistical Bureau (BPS) report. The result of this study showed, in 2016 there were decreasing poverty number on 21 Province compared with 2015 data. On the other hand, in 2017 compared with 2016, there were 14 Province experienced the increasing number on poverty. The conclusion of the result, which even the amount of tax revenue increased it does not mean the number of poverties will be reduce. The result gave the opportunity to the other research to find out behind the reason the phenomenon occurs. Keyword: Tax, poverty, education, welfare, public trust